2016
DOI: 10.13005/ojc/320446
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fatty Amine Chain Length on Synthesis Process of Inp/Zns Quantum Dots

Abstract: Obtaining narrow size distribution through conventional methods used for quantum dots of group II-VI semiconductors is impractical in the case of III-V semiconductors specially InP/ZnS quantum dots because of molecular precursors depletion and growth stage continuation through Ostwald ripening process. Using fatty amines as activator along with precursors can lead to more monodispersed quantum dots. In this work, the effect of fatty amine chain length on InP/ZnS quantum dots synthesis was investigated. Octylam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The chain length of alkylamines also plays an important role in controlling the morphology of nanoparticles [21]. It is reported that higher activation energy and low reaction rate of amine with a longer carbon chain leads to the formation of smaller-sized quantum dots due to its higher capping capacity [36,37]. Hence, in this study, the growth was restricted, and this resulted in the formation of irregular particles or anisotropic crystals.…”
Section: Mechanism For Morphology Evolution (Mechanism Of Formation O...mentioning
confidence: 80%
“…The chain length of alkylamines also plays an important role in controlling the morphology of nanoparticles [21]. It is reported that higher activation energy and low reaction rate of amine with a longer carbon chain leads to the formation of smaller-sized quantum dots due to its higher capping capacity [36,37]. Hence, in this study, the growth was restricted, and this resulted in the formation of irregular particles or anisotropic crystals.…”
Section: Mechanism For Morphology Evolution (Mechanism Of Formation O...mentioning
confidence: 80%